1999
DOI: 10.1002/(sici)1097-4547(19990601)56:5<471::aid-jnr3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and NGF synergistically protect terminally differentiated, ERα-transfected PC12 cells from apoptosis

Abstract: The potential cytoprotective effects of the gonadal steroid estrogen, acting via its receptor (ER) on target neurons, are of considerable interest in aging, disease, and trauma. In this study, we examined the effects of estrogen on a prototypical neuronal-like cell, namely, nerve growth factor (NGF) differentiated PC12 cells when these cells are placed into an apoptosis-inducing environment. A clonal line of PC12 cells stably transfected to express full-length rat ERalpha mRNA and protein (PCER cells), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…When NGF was systemically administered to healthy human subjects muscle pain particularly in the craniofacial region was observed but was more pronounced in females than in males (Petty et al , 1994). Interactions between NGF and oestrogen have been shown (Gollapudi and Oblinger, 1999) but the mechanisms involved in POMP are unclear.…”
Section: Pathophysiology Of Pompmentioning
confidence: 99%
“…When NGF was systemically administered to healthy human subjects muscle pain particularly in the craniofacial region was observed but was more pronounced in females than in males (Petty et al , 1994). Interactions between NGF and oestrogen have been shown (Gollapudi and Oblinger, 1999) but the mechanisms involved in POMP are unclear.…”
Section: Pathophysiology Of Pompmentioning
confidence: 99%
“…Other proposed mechanisms of protection by E2 include the suppression of excitotoxicity (Singer et al, 1996; Smith et al, 1987; Weaver et al, 1997), apoptosis (Alkayed et al, 2000; Alkayed et al, 2001), β amyloid toxicity (Goodman et al, 1996; Shi et al, 1998), edema formation (Roof et al, 1993; Roof et al, 1994), antioxidant production (Ayres et al, 1998; Bruce-Keller et al, 2000; Culmsee et al, 1999; Sawada et al, 1998) and regulation of growth factors (Gollapudi & Oblinger, 1999; Toran-Allerand, 1996). Finally, E2 is anti-inflammatory (Hunt et al, 1997; Ray et al, 1997; Salem et al, 2000; St Clair, 1997; Vegeto et al, 2001) in cerebral ischemia, reducing the number of active microglia (Lei et al, 2003), decreasing intravascular leukocyte adhesion and migration into brain (Santizo et al, 2000), and suppressing endothelial expression of adhesion molecules (Mori et al, 2004; Nathan et al, 1999).…”
Section: Mechanism Of Estradiol-mediated Neuroprotectionmentioning
confidence: 99%
“…This common pathway may explain the ability of E2 and neurotrophins to regulate the same broad array of cytoskeletal and growth-associated genes involved in neurite growth and differentiation. The interaction of E2 with growth factors may also prevent cell death by preventing initiation of apoptosis (Gollapudi & Oblinger, 1999). However, as mentioned above, E2 can also prevent neuronal cell death by directly regulating expression of effectors of cell death, such as members of the bcl-2 family of cell death-associated proteins (Alkayed et al, 2001b).…”
Section: E2 Neuroregeneration and Recoverymentioning
confidence: 99%
“…Studies in various systems have shown that estrogen protects neurons from insults including β‐amyloid peptide (Green et al . 1996), serum‐deprivation (Gollapudi and Oblinger 1999a), excitotoxicity (Singer et al . 1998), and oxidative stress (Moosmann and Behl 1999).…”
mentioning
confidence: 99%